The Effectiveness of Soursop Fruit Extract (Annona Muricata L) Against Uric Acid Levels in Male White Rats (Rattus Novergicus) - Feronika Bakari; Titin Dunggio; Rini Daud Supu (LP2M Universitas Bina Mandiri Gorontalo, 2021)
This study aims to determine whether there is a therapeutic effect on soursop (Annona Muricata L) juice in reducing uric acid levels in male white rats (Rattusnovergicus) and to determine what dose of bay leaf extract (Syzyzgiumpolyanthum) is effective in reducing acidity levels. veins in male white rats (Rattusnovergicus). The method in this study used a laboratory experiment with a post-test only control group design. The treatment groups were group I (negative control), group II (90 ml soursop juice), group III (180 ml soursop juice), group IV (soursop juice 270 ml). The results showed that soursop juice (Annona Muricata L) was positive for polyphenolic compounds. Statistical analysis of the data by KruskalWalis that 0.280 or > 0.05 means that there is a significant difference between uric acid levels before administration of soursop juice and uric acid levels after providing juice soursop fruit and continued with Duncan's analysis to see the difference in the effective dose.